2009
DOI: 10.1007/s10826-009-9275-9
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Youth at Risk for Treatment Failure in Outpatient Community Mental Health Services

Abstract: We developed predicted change trajectories and a warning system designed to identify psychotherapy cases at risk for treatment failure as observed in archival Youth Outcome Questionnaire data (parent/guardianreport) from 363 children and adolescents (ages 4-17) served in an outpatient community mental health system. We used multilevel modeling procedures to develop models of predicted change based on demographic information. Controlling for the effects of age on intercept, no other variables were significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 35 publications
3
36
0
Order By: Relevance
“…This optimism, however, stands in contrast to observations from the treatment outcome literature indicating that a significant proportion of clientsapproximately 5%-10% in adult studies-appear to get worse over the course of treatment (Lambert & Ogles, 2004;Lilienfeld, 2007;Mohr, 1995). Deterioration rates for children and adolescents served in community mental health settings appear to be particularly high, in some settings exceeding 20% (Warren, Nelson, & Burlingame, 2009;Warren, Nelson, Mondragon, Baldwin, & Burlingame, 2010). Labeled in various contexts as treatment failures, deteriorators, or not-on-track clients (Lambert & Ogles;Lilienfeld;Lambert, Whipple, Bishop, Vermeersch, Gray, & Finch, 2002), such cases have historically received little attention in treatment outcome research (Barlow, 2010;Lilienfeld).…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…This optimism, however, stands in contrast to observations from the treatment outcome literature indicating that a significant proportion of clientsapproximately 5%-10% in adult studies-appear to get worse over the course of treatment (Lambert & Ogles, 2004;Lilienfeld, 2007;Mohr, 1995). Deterioration rates for children and adolescents served in community mental health settings appear to be particularly high, in some settings exceeding 20% (Warren, Nelson, & Burlingame, 2009;Warren, Nelson, Mondragon, Baldwin, & Burlingame, 2010). Labeled in various contexts as treatment failures, deteriorators, or not-on-track clients (Lambert & Ogles;Lilienfeld;Lambert, Whipple, Bishop, Vermeersch, Gray, & Finch, 2002), such cases have historically received little attention in treatment outcome research (Barlow, 2010;Lilienfeld).…”
mentioning
confidence: 70%
“…We (Warren, Nelson, & Burlingame, 2009) used similar procedures in our initial effort to test an empirically derived warning system based on archival youth outcome data in a community mental health setting. The warning system correctly identified 71% of deteriorators; however, the sample was relatively small, and we believed that additional refinements to the system could yield increased prediction accuracy.…”
mentioning
confidence: 99%
“…Research indicates that when professionals learn to work with parents and leverage their strengths, more sustainable "anchoring" support contexts are created in the community (e.g. Netter Center for Community Partnerships, 2008;Warren, Nelson, & Burlingame, 2009). These anchoring supports facilitate the development of social capital and collective efficacy in the community while enhancing "horizontal" linkages between schools, health and human services, and youth development agencies (Alameda- Lawson & Alameda-Lawson, 2012).…”
Section: Collective Parental Engagementmentioning
confidence: 99%
“…Recent work has demonstrated the effectiveness of using early warning systems to identify adult clients at risk of treatment failure (Finch et al 2001;Lutz et al 2006;Shimokawa et al 2010). Also, Kazdin (2005, p. 255) suggested that tracking progress and providing feedback to clinicians about at-risk cases would be ''enormously helpful'' if used with children and adolescents as well, and a few studies have shown promising methods of using early warning systems with youth (Bishop et al 2005;Cannon et al 2010;Warren et al 2009). As an example, Cannon et al (2010) developed change trajectories using multilevel modeling on youth outcome data, then used these models as ''expected change trajectories'' that predicted, with high sensitivity rates, youth who were at risk for treatment failure.…”
Section: Administrative and Clinical Implicationsmentioning
confidence: 99%